Working in family firms: Less paid but more secure? Evidence from French matched employer-employee data - Andrea Bassanini; Eve Caroli; Antoine Rebérioux; Thomas Breda (Institute for the Study of Labor (IZA), 2011)
We study compensation packages in family and non-family firms. Using matched employer-employee data for a representative sample of French establishments, we first show that family firms pay on average lower wages to their workers. We find that part of this wage gap is due to differences in unobserved characteristics of workers across family and non-family firms. However, we also find evidence that company wage policies differ according to ownership status, so that workers staying in the same firm enjoy on average a 3% pay increase when a family firm becomes non-family owned and suffer a similar pay drop when the ownership transition occurs the other way round. In contrast, we find evidence that family firms are characterised by lower job insecurity, as measured by dismissal rates and by the subjective risk of dismissal perceived by workers. In addition, family firms appear to rely less on dismissals - and more on hiring reductions - than non-family firms when they downsize. We show that compensating wage differentials account for a substantial part of the inverse relationship between the family/non-family gaps in wages and job security.
urn:nbn:de:101:1-201107283654
Keywords: G34; J31; J33; J63; L26; 330; family firms; wages; job security; compensating wage differentials; linked employer-employee data